2014
DOI: 10.11604/pamj.2014.18.348.5136
|View full text |Cite
|
Sign up to set email alerts
|

La luxation chronique du coude chez l’enfant: à propos de 20 cas

Abstract: La luxation négligée du coude chez l'enfant est peu fréquente dans les pays industrialisés, elle n'est pas en revanche rare dans notre contexte. Nous rapportons une série de 20 cas, colligée au service d'Orthopédie Pédiatrique du CHU HASSAN II de Fès, sur une période de 4 ans. En effet, 14 malades étaient de sexe masculin, avec un âge moyen de 8,5 ans. Le mécanisme principal était la chute d'olivier. Le délai de consultation était très variable. 19 enfants ont été traités traditionnellement. La raideur constit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with those of other studies of NED in children which obtained good results with open reduction regardless of the duration of the symptoms (19,20). However, as reported by many authors, the complex NED is associated with poor outcomes (7,20).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are consistent with those of other studies of NED in children which obtained good results with open reduction regardless of the duration of the symptoms (19,20). However, as reported by many authors, the complex NED is associated with poor outcomes (7,20).…”
supporting
confidence: 93%
“…Irianto et al (19) have reported a ROM greater or equal to 70° in all patients treated for NED of beyond 3months, by open reduction. Attaraf et al (20) have reported very good and good results in 18 patients treated with open reduction. In our study, 10/26 have NED for more than 3 months, and 80% (8/10) have a good ROM at the last follow-up.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our patients presented with recent dislocations probably due to the proximity of hospitals in an urban setting. Chronic dislocations are more common in patients who reside in rural areas [8]. One of our patients had an elbow deformity while the other did not have any deformity.…”
Section: Discussionmentioning
confidence: 58%
“…In 1% of cases, the mechanism is unknown [5] [7]. In Africa, the fall of a tree is the most involved mechanism [8]. Which was the case for one of our patients.…”
Section: Discussionmentioning
confidence: 93%